Animals make us human : creating the best life for animals - Grandin, Temple; Johnson, Catherine, 1952- (Boston : Houghton Mifflin Harcourt, 2009)
Drawing on the latest research and her own work, Grandin identifies the core emotional needs of animals and explains how to fulfill them for dogs and cats, horses, farm animals, and zoo animals.
Includes bibliographical references (p. 308-328) and index.
Keywords: Emotions in animals; Animal behavior